Comparative study on management of acute moderate and severe lateral ankle sprain using immobilization in below knee slab versus stirrup ankle brace (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Amongst musculoskeletal injuries, ankle ligament sprains are the single most common  sports injury. However, there often appears to be no common regimen for their management, with a wide spectrum of treatment options available. The purpose of this study is to determine the functional outcome of the ankle joint after a moderate or severe inversion injury, comparing standard treatment with a Below Knee Slab Splint against a Stirrup ankle brace.Method: Prospective study conducted at the emergency department at Tribhuvan University Teaching Hospital. Fifty patients presenting consecutively were randomized into two equal groups: one group was treated with Below Knee Slab Splint and the other with an Stirrup ankle brace. All patients were given a standardized advice sheet referring to rest, ice, compression, and elevation, NSAIDS and support. Patients were reviewed after 48–72 hours, 14 days, and 3 week. Primary outcome measure: Ankle joint function assessed at 3 week using the modified Karlsson scoring method (maximum score 90). Secondary outcome measure: The difference in ankle girth (swelling) at 3 weeks. Results: Twenty-five patients in Below Knee Slab Splint group and twenty-five patients in the stirrup ankle brace group. The age of the patients ranged from 16 to 55 years with the mean of 30.68±9.33 years.The difference in mean age in years was not different in both groups (P>0.05).The distribution of gender and occupation in both groups were homogeneous (P>0.05). The karlsson’s score mean for brace group is 79.8±5.3 and for other group is 72.0±10.3 (p-value: 0.002). Thus there was a significant difference in Karlssons score between the two groups showing better functional improvement in patients receiving Stirrup ankle brace. There is significant difference in the swelling of clients in between application of the brace (1.00±0.48 and slab (1.70±0.50) the at end of the third week with p value 0.000.Conclusion: The use of Stirrup ankle brace for the treatment of lateral ligament ankle sprains produces a significant improvement in ankle joint function at three weeks compared with standard management with aimmobilization in below knee posterior slab splint.JSSN 2015; 18 (1), Page: 10-16